![4x-2y=48\\ \\ 2x+6y=-18](https://tex.z-dn.net/?f=4x-2y%3D48%5C%5C%20%5C%5C%202x%2B6y%3D-18)
First we'll multiply the second equation by -2
![-2\cdot (2x+6y)=-2\cdot -18\\ \\ -4x-12y=36](https://tex.z-dn.net/?f=-2%5Ccdot%20%282x%2B6y%29%3D-2%5Ccdot%20-18%5C%5C%20%5C%5C%20-4x-12y%3D36)
Now let's add the new equation and the first one.
![(4x-2y)+(-4x-12y)=48+36\\ \\ 4x-4x-2y-12y=48+36\\ \\ -14y=84\\ \\ y=\frac { 84 }{ -14 } \\ \\ y=-6](https://tex.z-dn.net/?f=%284x-2y%29%2B%28-4x-12y%29%3D48%2B36%5C%5C%20%5C%5C%204x-4x-2y-12y%3D48%2B36%5C%5C%20%5C%5C%20-14y%3D84%5C%5C%20%5C%5C%20y%3D%5Cfrac%20%7B%2084%20%7D%7B%20-14%20%7D%20%5C%5C%20%5C%5C%20y%3D-6)
We found y's value. We'll plug it in one of the equations to find x's value.
![y=-6\\ \\ 4x-2y=48\\ \\ 4x-2\cdot -6=48\\ \\ 4x+12=48\\ \\ 4x=48-12\\ \\ 4x=36\\ \\ x=\frac { 36 }{ 4 } \\ \\ x=9](https://tex.z-dn.net/?f=y%3D-6%5C%5C%20%5C%5C%204x-2y%3D48%5C%5C%20%5C%5C%204x-2%5Ccdot%20-6%3D48%5C%5C%20%5C%5C%204x%2B12%3D48%5C%5C%20%5C%5C%204x%3D48-12%5C%5C%20%5C%5C%204x%3D36%5C%5C%20%5C%5C%20x%3D%5Cfrac%20%7B%2036%20%7D%7B%204%20%7D%20%5C%5C%20%5C%5C%20x%3D9)
Solution ;
(9, -6)
Answer:
13
Step-by-step explanation:
First find the average the numbers (40 / 4 = 10)
2 are more and 2 are less
7, 9, 11, 13
Answer:
the answer is B. 75
Step-by-step explanation:
1000 this is because it is the right one